1991
DOI: 10.1136/gut.32.11.1352
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hypergastrinaemia in patients with colorectal cancer.

Abstract: Gastrin is trophic to colon cancers that possess gastrin receptors. Whether fasting serum gastrin concentrations are high in patients with colon cancer is controversial. We therefore studied the effect of food on serum gastrin concentrations in patients with colon cancer and control subjects. Fasting serum gastrin was greater, though not significantly so, in patients with colon cancer before surgery (mean (SD) 17*4 (3.6) pmoVI, n=16) compared with control subjects (12.6 (1.9) pmol/l, n=14). Postprandial increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 12 publications
3
29
0
Order By: Relevance
“…This result is keeping with findings by Wong et al 20 Other studies have been unable to demonstrate a decrease in plasma gastrin levels after apparently curative resection of colon cancer. 21,26 In our study, however, the postoperative gastrin levels remained persistently elevated and much higher in patients with colorectal cancer than in control (P<0.001).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This result is keeping with findings by Wong et al 20 Other studies have been unable to demonstrate a decrease in plasma gastrin levels after apparently curative resection of colon cancer. 21,26 In our study, however, the postoperative gastrin levels remained persistently elevated and much higher in patients with colorectal cancer than in control (P<0.001).…”
Section: Discussionsupporting
confidence: 80%
“…Similar findings with fasting and postprandial hypergastrinemia in patients with colon cancer have been shown by others, [16][17][18][19][20] although some other investigators have been unable to verify these results. [21][22][23] The aim of this study was to compare the serum gastrin levels (fasting and meal-stimulated) in patients with colorectal cancer and closely-matched control subjects.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Certainly, studies in colorectal cancer have shown low gastrin levels within the tumor and increased circulating nonamidated gastrin, i.e., only partially processed gastrin, suggesting that the tumor may be secreting gastrin with resulting hypergastrinemia [20]. This theory is supported by reports of reductions in serum gastrin levels after resection of primary colorectal tumors [21,22] although confl icting evidence exists [23,24]. Serum gastrin measurement may be unreliable for two reasons: commercial antisera react with amidated gastrin, and as nonamidated gastrin is the fully active biological entity, the results of such assays are suspect.…”
Section: Discussionmentioning
confidence: 49%
“…In vitro studies have shown that, in turn, hypergastrinemia promotes cell proliferation and cell migration and inhibits apoptosis-several factors that favour the development and progression of neoplasias of the gastrointestinal tract [18][19][20][21][22] . Animal models have demonstrated that ppis induce hypergastrinemia in mice and rats, enhance proliferation of colonic mucosa cells in those organisms, and promote adenoma progression [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%